Self-Efficacy dan Job Performance: a Meta Analysis - Lailla, Nor; Chudri, Intan Rizkia (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to explore the relationship between self-efficacy and job performance through a meta-analysis to provide an alternative and better understanding of the literature on self-efficacy and job performance. The research method used was a meta-analysis using JASP software. This study was conducted on 12 journals with 42 studies to examine the magnitude of the relationship between self-efficacy and job performance. The findings indicate a relationship between self-efficacy and job performance.